Den of wolves : a Blackthorn & Grim novel - Marillier, Juliet (Marillier, Juliet. Blackthorn & Grim novel, 2016)
"Healer Blackthorn knows all too well the rules of her bond to the fey: seek no vengeance, help any who ask, do only good. But after the recent ordeal she and her companion, Grim, have suffered, she knows she cannot let go of her quest to bring justice to the man who ruined her life. Despite her personal struggles, Blackthorn agrees to help the princess of Dalriada in taking care of a troubled young girl who has recently been brought to court, while Grim is sent to the girl's home at Wolf Glen to aid her wealthy father with a strange task--repairing a broken-down house deep in the woods. It doesn't take Grim long to realize that everything in Wolf Glen is not as it seems--the place is full of perilous secrets and deadly lies. Back at Winterfalls, the evil touch of Blackthorn's sworn enemy reopens old wounds and fuels her long-simmering passion for justice. With danger on two fronts, Blackthorn and Grim are faced with a heartbreaking choice--to stand once again by each other's side or to fight their battles alone."--